2020
DOI: 10.1111/tid.13275
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of deceased organ donors based on HIV, hepatitis B virus, and hepatitis C virus screening test results

Abstract: Background Potential deceased organ donors are screened for human immunodeficiency virus (HIV‐1), hepatitis B virus (HBV), and hepatitis C virus (HCV) with serologic tests and nucleic acid tests (NATs). The results of these tests on the utilization of donors have not been directly measured. Methods Twenty‐six organ procurement organizations (OPOs) provided primary HIV, HBV, and HCV screening results and utilization information for donor referrals evaluated from 2004 to 2017. Additional information regarding do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The value of NAT technology should be underlined by the fact that it might also be transferred beyond the scope of blood transfusions -organ utilization of HBV and/or HCV NAT-negative organs is increased over time despite positive antibody status (NAT-negative but seropositive), as reported based on evaluation of results and utilization information for organ donor referrals from 2004 to 2017, out of whom 1.8% were HCV antibody-positive and NATnegative (12). The use of NAT for deceased donor screening correlated with increased utilization of donor organs.…”
Section: Resultsmentioning
confidence: 99%
“…The value of NAT technology should be underlined by the fact that it might also be transferred beyond the scope of blood transfusions -organ utilization of HBV and/or HCV NAT-negative organs is increased over time despite positive antibody status (NAT-negative but seropositive), as reported based on evaluation of results and utilization information for organ donor referrals from 2004 to 2017, out of whom 1.8% were HCV antibody-positive and NATnegative (12). The use of NAT for deceased donor screening correlated with increased utilization of donor organs.…”
Section: Resultsmentioning
confidence: 99%
“…The global prevalence of HBsAg-positive donors ranges from 0.5% to 7% among all potential donors, they are relatively common in endemic regions, such as the Far East and the Mediterranean basin [ 50 ]. Provided strict selection criteria are used, such as the absence of hepatitis delta infection in donors and recipients and/or the absence of significant fibrosis of the graft, the use of organs from HBsAg-positive donors is associated with favorable outcomes [ 51 , 52 ]. However, a case report showed a good result after LT of a HDV-coinfected patient who received a HbsAg-negative HBV-DNA positive graft.…”
Section: Patients Receiving Hbsag-positive Graftsmentioning
confidence: 99%
“…HCV‐negative recipients of organs from HCV‐aviremic donors have low likelihood of infection without risk factors for acute donor HCV infection (e.g., death from drug overdose) [74, 84]. In a study of serologies for potential donor organs screened from OPOs from 2004–2017, Theodoropoulos et al [85] demonstrated an increase in utilization of HCV‐aviremic donors after the use of NAT screening.…”
Section: Hepatitis C Positive‐to‐negative Transplantationmentioning
confidence: 99%